The Impact of Shear Reinforcement Amount and Arrangement on the Shear Capacity of Shallow RC Beams: An Experimental Study - Ahmed A. Soliman; Dina M. Mansour; Ayman H. Khalil; Ahmed Ebid (Salehan Institute of Higher Education, 2023)
This study investigates the impact of shear reinforcement amount and arrangement on the shear capacity of shallow/wide RC beams. Seven specimens of shallow/wide beams with different ultimate shear reinforcement stress (μ.Fys), longitudinal spacing to depth ratio (S/d), and transversal spacing to depth ratio (S’/d) were tested under a monotonic three-point bending test. All the specimens were designed to fail at shearing. The results showed that the shear reinforcement was fully functioning until it yielded; also, the amount of shear reinforcement had the major impact on the shear capacity; in addition, the transverse spacing had more influence on the shear capacity than the longitudinal spacing. The measured shear capacities were compared to six design codes, in which the results ranged from 95% to 110%, with the Japanese code (JSCE) being the closest to the experimental results. Two AI-based predicting equations, “Genetic Programming” (GP) and “Evolutionary Polynomial Regression” (EPR), were also compared to the experimental, with accuracies of 78% and 86% of the measured capacities, respectively. Initial stiffness, final stiffness, dissipated energy, and ductility were all discussed for the seven specimens, with ultimate shear reinforcement stress being the most impactful on the total shear capacity of the wide beams. Doi: 10.28991/CEJ-2023-09-12-013 Full Text: PDF